Severe multivessel coronary artery spasm detected by computed tomography: a case report - Jin, Cai De (Eur Heart J Case Rep, 2020)
BACKGROUND: Ventricular arrhythmia and sudden cardiac arrest caused by multivessel coronary artery spasm (CAS) is rare. Although coronary angiography (CAG) with provocation testing is the diagnostic gold standard in current vasospastic angina guidelines, it can cause severe procedure-related complications. Here, we report a novel technique involving dual-acquisition coronary computed tomography angiography (CCTA) to detect multivessel CAS in a patient who survived out-of-hospital cardiac arrest (OHCA). CASE SUMMARY: A 58-year-old healthy Korean male survived OHCA caused by ventricular fibrillation (VF), experiencing seven episodes of defibrillation and cardiopulmonary resuscitation, and was referred to the Emergency Room. Vital signs were stable and physical examination, electrocardiogram, chest, and brain CT did not show any abnormal findings, except elevated hs-Troponin I levels (0.1146 ng/mL). Echocardiogram revealed a regional wall motion abnormality in the inferior wall, with a low normal left ventricular ejection fraction (50%). A multivessel CAS (both left and right) was detected using a dual-acquisition CCTA technique (presence and absence of intravenous nitrate). During CAG with the 2(nd) injection of ergonovine, a prolonged and refractory total occlusion in the proximal-ostial right coronary artery was completely relieved after a seven-cycle intracoronary injection regimen of nitroglycerine. The patient was discharged with the recommendation of smoking and alcohol cessation. Nitrate and calcium channel blockers were also prescribed. The patient had no further events at 3 months of follow-up after discharge. DISCUSSION: Dual-acquisition CCTA is a promising tool to detect multivessel CAS.